IMPLEMENTASI PERATURAN GUBERNUR KALIMANTAN TIMUR NOMOR 75 TAHUN 2011 TENTANG PEDOMAN PENYUSUNAN PENETAPAN KINERJA DAN PELAPORAN AKUNTABILITAS KINERJA INSTANSI PEMERINTAH DI LINGKUNGAN PEMERINTAH PROVINSI KALIMANTAN TIMUR PADA SEKRETARIAT DAERAH PROVINSI KALIMANTAN TIMUR - Adriani . (Jurnal Paradigma (JP), 2017)
The purpose of this study is to explore and analyze the implementation of East Kalimantan Governor’s Law No.75, 2011 on The Guidelines of The Creation of Performance Arrangement and Accountability Report in East Kalimantan Government Agencies. Sources of the data taken from the key informants. This research used interactive model developed by Milles, Huberman and Saldana to analyze the data that were teken.